Feasibility of Opportunity Material Module with Joymath Cognitive Behavioral Method to Reduce Mathematics Anxiety and Increase Student Self-Efficacy - Marhaeni, Nafida Hetty; Khuzaini, Nanang; Rizky, Muhammad Rafi Fajar; Yuniasanti, Reny; Akbar, Mutaqin; Sari, Dian Kartika; Dangin, Dangin (Mosharafa: Jurnal Pendidikan Matematika, 2024)
Siswa memerlukan media pembelajaran yang dapat membantu siswa mengurangi kecemasan matematika dan meningkatkan efikasi diri. Tujuan penelitian yaitu mengembangkan modul untuk mengurangi kecemasan matematika dan meningkatkan efikasi diri siswa pada materi peluang. Penelitian Research and Development ini menggunakan model ADDIE dengan lima tahap pengembangan yaitu analisis, desain, pengembangan, implementasi, dan evaluasi. Sumber data dan subjek dalam penelitian ini adalah ahli materi, ahli media, guru, dan 1328 siswa dari 24 SMP di Kota Yogyakarta. Teknik pengumpulan data yang digunakan yaitu wawancara, observasi, Focus Group Discussion (FGD), dan angket. Hasil menunjukkan bahwa produk yang dikembangkan yaitu modul materi peluang untuk mengurangi kecemasan matematis dan meningkatkan efikasi diri siswa layak digunakan dalam pembelajaran matematika. Pengambilan keputusan kelayakan produk didasarkan pada hasil analisis penilaian dari validator, ahli materi, dan ahli media yang menunjukkan bahwa modul sangat valid dan berpeluang menurunkan kecemasan matematis dan meningkatkan efikasi diri siswa.Students need learning media that can help students reduce mathematics anxiety and increase self-efficacy. The aim of the research is to develop a module to reduce mathematics anxiety and increase students' self-efficacy in opportunity material. This Research and Development research uses the ADDIE model with five development stages, namely analysis, design, development, implementation and evaluation. The data sources and subjects in this research were material experts, media experts, teachers, and 1328 students from 24 junior high schools in Yogyakarta City. The data collection techniques used were interviews, observation, Focus Group Discussion (FGD), and questionnaires. The results show that the product developed, namely the opportunity material module to reduce mathematical anxiety and increase students' self-efficacy, is suitable for use in mathematics learning. Decision making on product feasibility is based on the results of assessment analysis from validators, material experts and media experts which show that the module is very valid and has the opportunity to reduce mathematical anxiety and increase student self-efficacy.